Molecular modeling of Bcl-xL post-translational modifications and of keteniminium salts - Tanrıver, Gamze. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Computational chemistry plays an important role in deciphering the structural proper ties of systems by using different approaches, such as quantum mechanics (QM) and molecular mechanics (MM) and gives insight by mimicking their dynamic environments. This dissertation contains two main topics, namely investigation of Bcl-xL deamidation via molec ular dynamics (MD) simulations and investigation of keteniminium salts via QM methods. Investigation of post-translational modifications (PTMs) is important to understand their role on the structure and function of proteins. Deamidation, one of the PTMs is a crucial switch used for regulating the biological function of anti-apoptotic Bcl-xL. In the first part of the thesis, deamidation-induced conformational changes in Bcl-xL were explored to gain insight into its loss of function by performing MD simulations. MD outcomes suggest that deamidation allosterically causes remarkable changes in conformation, interaction, and dynamics of Bcl-xL and conceivably impair its function. This study will provide a unique perspective on the underlying mechanism of Bcl-xL deamidation-induced cell death. Keteniminium salts (KIs), nitrogen analogues of ketenes are widely used intermediates for the synthesis of various organic substances due to their higher electrophilicity, reactivity and regioselectivity. In the second part of the thesis, KIs were scrutinized, from their forma tion mechanisms to their involvement in organic reactions, by means of a DFT study. Exper imentally observed reactivity differences in the [2 + 2] cycloaddition and electrocyclization reactions were rationalized via a range of different analysis techniques. The outcomes of this study are expected to contribute to the understanding of the formation mechanism as well as the reactivity differences of keteniminium salts and aid synthetic applications.
Keywords: Quantum theory.; Computational chemistry.